Rancang Bangun Sistem Informasi Manajemen Inventory Bahan Baku Berbasis Web Pada Toko Roti Andika - Ika Ayu Pertiwi; Eko Purwanto; Sundari Sundari (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2026)
Toko Roti Andika faced challenges in inventory control that was still carried out conventionally based on the owner's estimates, a condition that had the potential to create an imbalance between the available stock and actual needs, while also resulting in operational budget waste. As an effort to address these problems, a web based inventory management information system was developed using the Prototype approach by utilizing the Laravel framework as the development framework and MySQL as the data storage database. The designed system integrates three inventory calculation methods, namely Economic Order Quantity (EOQ), Safety Stock, and Reorder Point (ROP) as the basis for raw material procurement decision making. The system supports three user roles with different access rights, namely Owner, Warehouse Admin, and Production Staff. Through this system, inventory management can be carried out digitally and in real-time, ranging from raw material request submissions, stock transaction recording, to EOQ based reorder recommendations. The initial testing results demonstrate that the system successfully replaces manual inventory management, enhances the accuracy of record-keeping, and supports more structured and efficient decision-making in raw material procurement.